Anthropogenic edge effects and aging errors by hunters can affect the sustainability of lion trophy hunting - Loveridge, A; Wijers, M; Mandisodza-Chikerema, R; Macdonald, D; Chapron, G (Springer Nature, 2023)
Many large predator populations are in decline globally with significant implications for ecosystem integrity and function. Understanding the drivers of their decline is required to adequately mitigate threats. Trophy hunting is often cited as a tool to conserve large mammal populations but may also have negative impacts if not well managed. Here we use a spatially implicit, individual based model to investigate the threats posed to African lion populations by poorly managed trophy hunting and additive anthropogenic mortality such as poaching and retaliatory killing. We confirm the results of previous studies that show that lion trophy hunting can be sustainable if only older male lions are hunted, but demonstrate that hunting becomes unsustainable when populations are exposed to additional anthropogenic mortality, as is the case for most free ranging populations. We show that edge effects can be a critical determinant of population viability and populations that encompass well protected source areas are more robust than those without. Finally, errors in aging of hunted lions by professional trophy hunters may undermine the sustainability of the age-based quota setting strategies that are now widely used to manage lion trophy hunting. The effect of aging errors was most detrimental to population persistence in the ≥ 6 and ≥ 7 year-old age thresholds that are frequently used to define suitably aged lions for hunting. Resource managers should limit offtakes to older demographics and additionally take a precautionary approach when setting hunting quotas for large carnivore populations that are affected by other sources of anthropogenic mortality, such as bush-meat poaching, retaliatory killing and problem animal control.